Peran Gaya Kepemimpinan Transformasional dan Transaksional dalam Meningkatkan Kinerja Pegawai - Yofitri Heny Wahyuli (Spirit Publik: Jurnal Administrasi Publik, 2023)
Employee performance is one factor that is quite important in the development of the company. Employee performance is influenced by many factors and one of them is the transaction leadership style and the transformation leadership style. This study aims to determine the Transformation Leadership Style and Transaction Leadership Style on Employee Performance at PT. Semen Baturaja (Persero) Tbk Palembang. With the number of respondents as many as 9 respondents. The type of research used in this research is qualitative research using descriptive qualitative methods. The results in this study indicate that the Transformation Leadership Style and the Transaction Leadership Style influence employee performance both partially and simultaneously. The test results of the coefficient of determination show that the transaction leadership style and the transformation leadership style are able to explain the employee's performance by 73.8%. With the results of the research that has been done, for the leaders of PT. Semen Baturaja (Persero) Tbk Palembang should improve transformation and transaction leadership styles because both have a positive effect on employee performance, if you look at the research results transformation leadership style has a more positive effect on improving performance but remember that effective leadership is a combination of the two leadership styles.